On the Role of Internationalization of Firm-Level Corporate Governance – The Case of Audit Committees - Haroon Afzali; Minna Martikainen; Lars Oxelheim; Trond Randøy (Research Institute of Industrial Economics (IFN), 2020)
Motivated by agency theory and arguments from linguistic studies, we argue in this paper the internationalization of a firm's audit committee to be associated with weaker firm-level corporate governance. Based on 2,015 publicly traded European firms from 16 countries over 2000-2018, we find the presence of foreign directors on audit committees to have a significant negative impact on financial reporting quality (FRQ). The effect is found to be weaker in countries with strong investor protection. We find linguistic differences within audit committees an important explanation for the negative influence of foreign directors on FRQ. The results are robust to alternative FRQ measures and model specifications, including difference-in-differences and propensity score matching. While foreign directors on a corporate board may create value for the firm by boosting the advisory capacity of that board, recruiting a foreign director to that firm's audit committee may compromise the board's monitoring function and the firm's FRQ.
Keywords: F23; G34; K22; M16; M42; 330; Reporting Quality; Foreign Directors; Audit Committee; Investor Protection